2023
DOI: 10.3233/idt-220310
|View full text |Cite
|
Sign up to set email alerts
|

Disaster tweet classification: A majority voting approach using machine learning algorithms

Abstract: Nowadays, people share their opinions through social media. This information may be informative or non-informative. Filtering informative information from social media plays a challenging issue. Nevertheless, people will interact more with that particular disaster event on social media, primarily when a disaster occurs. They share their opinion through some textual information such as tweets or posts. In this work, we propose a generalized approach for categorizing the informative and non-informative media on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The authors used lexicons and TF-IDF features with six ML models and revealed that their framework outperformed the baselines. Later, a majority voting-based approach is presented in Krishna, Srinivas & Prasad Reddy (2022) to identify only informative tweets using word2vec, TF-IDF, and the Glove model. Their model showed significant performance but they did not handle infrastructure and human damages.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors used lexicons and TF-IDF features with six ML models and revealed that their framework outperformed the baselines. Later, a majority voting-based approach is presented in Krishna, Srinivas & Prasad Reddy (2022) to identify only informative tweets using word2vec, TF-IDF, and the Glove model. Their model showed significant performance but they did not handle infrastructure and human damages.…”
Section: Related Workmentioning
confidence: 99%
“… Priya et al (2018) developed a query-based information retrieval method for infrastructural damage assessment but did not address human damage. Moreover, few studies proposed approaches for informational vs non-informational tweet identification like the majority voting approach ( Krishna, Srinivas & Prasad Reddy, 2022 ), and multi-model approach using image and text data ( Koshy & Elango, 2023 ) but did not address human damage assessment. According to our knowledge, only one study, Madichetty & Sridevi (2021) , focused on damage assessment for infrastructural and human damages from tweets and used a lexicon and frequency-based approach (hand-crafted) with traditional machine learning (ML) models.…”
Section: Introductionmentioning
confidence: 99%